2012
DOI: 10.1016/j.jhealeco.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Does retirement affect cognitive functioning?

Abstract: This paper analyses the effect of retirement on cognitive functioning using a longitudinal survey among older Americans, which allows controlling for individual heterogeneity and endogeneity of the retirement decision by using the eligibility age for social security as an instrument. The results highlight a significant negative effect of retirement on cognitive functioning. Our findings suggest that reforms aimed at promoting labour force participation at an older age may not only ensure the sustainability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
313
4
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(354 citation statements)
references
References 54 publications
(22 reference statements)
18
313
4
8
Order By: Relevance
“…In individuals with healthy cognitive functioning, these mechanisms contribute to the adaptation of brain activity when the task difficulty level is increased and thereby enhance cognitive performance [4]. Empirically corroborating the predictions of the cognitive reserve concept, both correlational and causal evidence showed that longer education in early life, cognitively demanding occupation in midlife, and cognitive leisure activity in midlife and old age contribute to the buildup of cognitive reserve during the life course and are related to better cognitive functioning such as memory and executive functioning in old age [5,6,7,8,9,10,11,12,13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 95%
“…In individuals with healthy cognitive functioning, these mechanisms contribute to the adaptation of brain activity when the task difficulty level is increased and thereby enhance cognitive performance [4]. Empirically corroborating the predictions of the cognitive reserve concept, both correlational and causal evidence showed that longer education in early life, cognitively demanding occupation in midlife, and cognitive leisure activity in midlife and old age contribute to the buildup of cognitive reserve during the life course and are related to better cognitive functioning such as memory and executive functioning in old age [5,6,7,8,9,10,11,12,13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 95%
“…In individuals with healthy cognitive functioning, these mechanisms contribute to the adaptation of brain activity when the task difficulty level is increased and thereby enhance cognitive performance [4]. Empirically corroborating the predictions of the cognitive reserve concept, evidence showed that longer education in early life, cognitively demanding jobs in midlife, and leisure activities in midlife and old age contribute to cognitive reserve during the life course and are related to better cognitive functioning such as memory and executive functioning in old age [5-17]. Another research line related to the concept of reserves concerns social capital [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have found that working until higher ages results in greater investment in cognitive skills, higher participation in on-the-job-training, healthier lifestyles, and greater mental activity levels (Bonsang, Adam, and Perelman 2012). The large differences in sexspecific employment, in particular the entry of the female population into the labour market that has taken place at different times across the countries considered (Boeri, Del Boca, and Pissarides 2005), may additionally account for cross-country variation in cognition.…”
Section: Summary and Discussionmentioning
confidence: 99%